Modeling Family Quality of Life Based on Economic Pressure, Family Adaptability, Hope, and Emotional Support: The Mediating Role of Psychological Well-Being - Salonen, Mikko; Desrosiers, Liam; Leitner, Stefan (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to develop and test a structural model of family quality of life based on economic pressure, family adaptability, hope, and emotional support, while examining the mediating role of psychological well-being among married adults in Canada.Methods and Materials: This study employed a cross-sectional correlational design using structural equation modeling (SEM). The study population consisted of married adults residing in Canada. A total of 612 individuals were recruited through community organizations and online platforms, of whom 587 participants met the inclusion criteria and were retained for analysis. Data were collected using standardized instruments measuring family quality of life, economic pressure, family adaptability, hope, emotional support, and psychological well-being. Descriptive statistics, Pearson correlation analyses, confirmatory factor analysis, and structural equation modeling were conducted using SPSS 29 and AMOS 29. The significance of indirect effects was assessed through bootstrap analysis with 5,000 resamples.Findings: The measurement model demonstrated excellent fit to the data (χ²/df = 2.41, CFI = .956, TLI = .949, RMSEA = .049, SRMR = .042). The structural model also exhibited satisfactory fit indices (χ²/df = 2.53, CFI = .951, TLI = .947, RMSEA = .051, SRMR = .044). Economic pressure significantly and negatively predicted psychological well-being (β = −.28, p < .001) and family quality of life (β = −.21, p < .001). Family adaptability positively predicted psychological well-being (β = .24, p < .001) and family quality of life (β = .18, p < .001). Hope showed significant positive effects on psychological well-being (β = .35, p < .001) and family quality of life (β = .16, p < .001). Emotional support positively predicted psychological well-being (β = .27, p < .001) and family quality of life (β = .14, p = .001). Psychological well-being emerged as the strongest direct predictor of family quality of life (β = .49, p < .001). Bootstrap analyses confirmed significant indirect effects of all predictor variables on family quality of life through psychological well-being (p < .001). The model explained 69% of the variance in psychological well-being and 74% of the variance in family quality of life.Conclusion: The findings indicate that family quality of life is shaped by the combined influence of economic, familial, and psychosocial factors. Psychological well-being plays a central mediating role, transforming the effects of economic pressure, family adaptability, hope, and emotional support into family quality-of-life outcomes. Interventions aimed at strengthening psychological well-being, fostering hope, enhancing emotional support, and promoting adaptive family functioning may substantially improve family quality of life while mitigating the negative effects of economic stress.